2007
DOI: 10.1002/ijc.22485
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case–control study of the use of hormone‐related supplements and association with breast cancer

Abstract: Hormone-related supplements (HRS), many of which contain phytoestrogens, are widely used to manage menopausal symptoms, yet their relationship with breast cancer risk has generally not been evaluated. We evaluated whether use of HRS was associated with breast cancer risk, using a population-based case-control study in 3 counties of the Philadelphia metropolitan area consisting of 949 breast cancer cases and 1,524 controls. Use of HRS varied significantly by race, with African American women being more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 26 publications
2
57
3
3
Order By: Relevance
“…To date, one observational study has investigated the invasive breast cancer risk with respect to menopausal HEP use (17). Concordant with our finding, a preventive effect of ever use of any HEP was observed in that study (OR, 0.65; 95% CI, 0.49-0.87), which was slightly larger than the effect in our study.…”
Section: Cancer Epidemiol Biomarkers Prev 2009;18(8) August 2009supporting
confidence: 91%
See 1 more Smart Citation
“…To date, one observational study has investigated the invasive breast cancer risk with respect to menopausal HEP use (17). Concordant with our finding, a preventive effect of ever use of any HEP was observed in that study (OR, 0.65; 95% CI, 0.49-0.87), which was slightly larger than the effect in our study.…”
Section: Cancer Epidemiol Biomarkers Prev 2009;18(8) August 2009supporting
confidence: 91%
“…In a recent clinical study, an isopropanolic extract of black cohosh (Remifemin) had no effect on breast density or cell proliferation in postmenopausal women (16), whereas observational studies have shown protective effects on occurrence and recurrence of invasive breast cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Cimicifuga racemosa (L) Nutt]. Recent studies indicate that black cohosh may have chemopreventive and chemotherapeutic potential [73,74] . Actein was found to inhibit the growth of p53-positive HepG2 cells with an IC50 value of 27 μg/mL [75] .…”
Section: Triterpenesmentioning
confidence: 99%
“…There are few reports of OBS use by breast cancer patients. In a casecontrol study [38], 17.2% of breast cancer cases were found to use hormone-related supplements, while as part of the HEAL study 34.7% of 502 postmenopausal women with in situ and invasive breast cancers reported taking at least one oestrogenic supplement since diagnosis [39]. Direct comparison between studies is, however, difficult due to differences in characterisation and grouping of supplements.…”
Section: Supplement Use Before and After Diagnosismentioning
confidence: 99%